A Cross-Sectional Study on Menstrual Pattern among Adolescent Girls in Aligarh - Farha Tarannum; Najam Khalique; Uzma Eram (Medsci Publications, 2020)
Background: Adolescents (10-19 years) constitute 21.3% of total population of India. Major biological milestone in this period is the beginning of menstruation The menstrual cycle are characterized by variability in volume, pattern and regularity. There are few research on menstrual pattern of adolescent girls. Hence this study will highlight the menstrual pattern and factors affecting it. Methods:  A descriptive cross-sectional study in schools under Aligarh Muslim University, Aligarh was undertaken. A total of 422 girls were taken by systematic random sampling with probability proportionate to size. Data was analysed statistically by bivariate analysis and multivariate (binary) logistic model by backward LR method using SPSS Version 20. Results: 39.1% of girls experienced irregular cycle. Heavy bleeding was reported by 25.6% girls and 18.7% had scanty bleeding. Irregular cycle was 4.25 times in underweight and 2.19 times in overweight/obese compared to normal body mass index. There was 46% reduction in irregular cycle for those who attained menarche for more than 2 years. Conclusion: There are many host factors which influence menstrual pattern in girls. These factors increases the girls risk for various reproductive disorders in future.